Queensland Fruit Fly, Bactrocera tryoni (Froggatt) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
The Queensland fruit fly, Bactrocera tryoni (Froggatt), occurs in climates ranging from temperate to tropical. Within its range, it is one of the most important pests with which pome and stone fruit growers have to contend, and at times it has been a very destructive pest of citrus. Bactrocera tryoni appears to be almost as destructive to fruit production in its Australian range as the oriental fruit fly, Bactrocera dorsalis Hendel, is in countries where it appears. A heavy outbreak of B. tryoni in New South Wales during 1940-41 resulted in the rejection of 5 to 25% of citrus at harvest. It is not established in the United States, but the extensive damage caused by the larvae of this fly in areas similar to Florida where it has become established indicates that this species could become a serious pest of pome and stone fruit crops, and possibly of citrus, if it were to become established in Florida. This document is EENY-259 (originally published as DPI Entomology Circular 34), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.